The Effect of Supervision, Work Discipline and Career Development on the Performance of Employees of BPKD Office Seluma Distric - Yulia Hartuti; Ida Anggriani; Nurzam Nurzam (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The analytical method used is the validity test, reliability test, simple linear regression, coefficient of determination, F test and t test. Based on the results of the study, it shows that Supervision (X1) partially has a significant effect on employee performance (Y) at BPKD Office Seluma Distric because the significant value is 0.001 < 0.05. Work discipline (X2) partially has a significant effect on employee performance (Y) at BPKD Office Seluma Distric because the significant value is 0.025 < 0.05. Career development (X3) partially has a significant effect on employee performance (Y) at the BPKD Office Seluma Distric because the significant value is 0.002 < 0.05. Supervision variables (X1), work discipline (X2) and career development (X3) simultaneously or together have a significant effect on employee performance (Y) at BPKD Office Seluma Distric because the significant value is 0.000 < 0.05.